2017
DOI: 10.1007/s10551-017-3768-z
|View full text |Cite
|
Sign up to set email alerts
|

State-Owned Enterprises as Bribe Payers: The Role of Institutional Environment

Abstract: Our paper draws attention to a neglected channel of corruptionthe bribe payments by state-owned enterprises (SOEs). This is an important phenomenon as bribe payments by SOEs fruitlessly waste national resources, compromising public welfare and national prosperity. Using a large dataset of 30,249 firms from 50 countries, we show that, in general, SOEs are less likely to pay bribes for achieving organizational objectives owing to their political connectivity. However, in deteriorated institutional environments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 141 publications
(196 reference statements)
0
35
0
Order By: Relevance
“…Clearly, a society’s institutional context matters ( Montinola and Jackman, 2002 ; Adelopo and Rufai, 2020 ). Second, in case of organization-level bribery, a meso lens is needed as organizational factors are argued to play an important role as well ( den Nieuwenboer and Kaptein, 2008 ; Shaheer et al, 2019 ). Third, a micro perspective is required to understand individual variation within countries and across organizational contexts, as not all people equally engage in bribery within the same institutional and organizational environment ( Navot et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, a society’s institutional context matters ( Montinola and Jackman, 2002 ; Adelopo and Rufai, 2020 ). Second, in case of organization-level bribery, a meso lens is needed as organizational factors are argued to play an important role as well ( den Nieuwenboer and Kaptein, 2008 ; Shaheer et al, 2019 ). Third, a micro perspective is required to understand individual variation within countries and across organizational contexts, as not all people equally engage in bribery within the same institutional and organizational environment ( Navot et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Business ethics differ between state-owned enterprises and the private sector. Research results in China showed that private companies are more prone to illegal activity in response to institutional limitations compared to state-owned enterprises [ 138 , 139 ]. Ip [ 140 ] concluded that there are high ethical standards for business in well-managed state-owned enterprises.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…For example, organizational commitment in state-owned enterprises more often results in positive behaviors toward other people rather than tasks related to an organization [ 150 ]. This is not to say that there is no unethical behavior in SOEs, but its character is different from UPB [ 151 , 152 ]. Inter alia, the overclaiming happening among employees of SOEs has a significant influence on their ethical behavior [ 153 ].…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…This means managers have no incentive to maximize the value creation process. Corporate governance and the structure of the board can help to control the behavior of directors (Shaheer et al, 2019).…”
Section: The Empirical Investigations Into Political Connectionmentioning
confidence: 99%